Factors of price convergence and its estimated level in Hungary - Péter Bauer (Magyar Nemzeti Bank, 2015)
The study analyses the relationship between real economy convergence and the convergence of relative prices. Similar to its peers in the CEE region, a significant part of Hungary's price convergence with developed Western European countries can be attributed to the convergence of the real economy. The crisis, however, impeded catching-up in the entire region, leaving relative prices largely unchanged in the subsequent periods. In addition to decelerating real convergence, this may also have resulted from depreciating nominal exchange rates. The relationship between relative price levels and economic development is often explained by the Balassa-Samuelson effect; according to the findings, however, this effect accounts for only a part of the real appreciation observed in the region over the past one-and-a-half decades. This may have resulted primarily from problems concerning the data required for the estimation of the Balassa-Samuelson effect. Thus, in interpreting the findings, the main focus is a direct estimation of the relationship between relative price levels and economic development. The rate of expected price convergence in Hungary can be calculated from assumptions about future economic growth, relying on estimates pertaining to the relationship between relative price levels and economic development. According to our estimates, real convergence may be accompanied by price convergence of 0.5-1 per cent per annum. This calculation, however, involves significant uncertainty. The lower growth rate of regulated prices may lead to lower convergence rates, while higher economic growth compared to the euro area may drive faster price convergence.
Keywords: E31; 330; price convergence; Balassa-Samuelson effect; real appreciation